Pemanfaatan Teknologi Informasi dalam Pembelajaran Pendidikan Islam: Analisis Tantangan dan Potensi - Maryam, Siti; Yasin, Muhammad (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
This study focuses on the use of information technology in Islamic Education learning at SMAN 1 Sangatta Utara and SDN 011 Sangatta Utara. The background of this study is the importance of information technology as a main pillar in the transformation of the education system, especially Islamic Education, amidst the challenges of the digital divide and uneven infrastructure. The formulation of the problem includes the level of understanding and skills of teachers in utilizing information technology, the tools and platforms used, and the challenges faced in the process of integrating the technology. The results of the study show that the majority of teachers have utilized digital platforms such as PowerPoint and Canva to support learning. At SMAN 1 Sangatta Utara, the use of information technology helps teachers in delivering material interactively, while at SDN 011 Sangatta Utara, the use of technology faces obstacles such as slow internet connections and limited teacher training. The main obstacles are the lack of adequate training and infrastructure, especially in elementary schools. These findings emphasize the need for ongoing technology training to improve teacher competence and provide more evenly distributed infrastructure. In addition, the potential of information technology as a learning aid for Islamic Education is very large if these challenges can be overcome.